Impact of recent lake eutrophication on microbial community changes as revealed by high resolution lipid biomarkers in Rotsee (Switzerland) - Naeher, Sebastian; Smittenberg, R.; Gilli, A.; Kirilova, E.; Lotter, A.; Schubert, C. (Pergamon, 2012)
The effects of eutrophication on short term changes in the microbial community were investigated using high resolution lipid biomarker and trace metal data for sediments from the eutrophic Lake Rotsee (Switzerland). The lake has been strongly influenced by sewage input since the 1850s and is an ideal site for studying an anthropogenically altered ecosystem. Historical remediation measures have had direct implications for productivity and microbial biota, leading to community composition changes and abundance shifts. The higher sewage and nutrient input resulted in a productivity increase, which led predominantly to a radiation in diatoms, primary producers and methanogens between about 1918 and 1921, but also affected all microorganism groups and macrophytes between about 1958 and 1972. Bacterial biomass increased in 1933, which may have been related to the construction of a mechanical sewage treatment plant. Biomarkers also allowed tracing of fossil organic matter/biodegraded oil contamination in the lake. Stephanodiscus parvus, Cyclotella radiosa and Asterionella formosa were the dominant sources of specific diatom biomarkers. Since the 1850s, the cell density of methanogenic Archaea (Methanosaeta spp.) ranged within ca. 0.5–1.8 × 109 cells g−1 dry sediment and the average lipid content of Rotsee Archaea was ca. 2.2 fg iGDGTs cell−1. An altered BIT index (BITCH), indicating changes in terrestrial organic matter supply to the lake, is proposed.